The synthesis and evaluation of thiolated alginate as the barrier to block nutrient absorption on small intestine for body‐weight control - Tzu‐Chien Chen; Rui‐Chian Tang; Jhih‐Ni Lin; Wei‐Ting Kuo; I‐Hsuan Yang; Ya‐Jyun Liang; Feng‐Huei Lin (Wiley, 2023)
Abstract Obesity is the most common health concern all over the world. However, till now, there is no promising way to manage obesity or body‐weight control. The aim of the study is to develop an edible gel as a health supplement that temporarily attaches to the mucus of the intestines, forming an absorption barrier to block the nutrients. We modify the alginate with the thiol group as thiolated alginate (TA) that may stay on the mucosa layer for a much longer time to reduce nutrient absorption. In this study, the TA is synthesized successfully and proved a good mucosal adhesion to serve as a barrier for nutrient absorption both in vitro and in vivo. The results of in vivo imaging system (IVIS) show that the synthesized TA can be exiled from the gastrointestinal tract within 24 h. The animal study shows that the TA by daily oral administration can effectively reduce body weight and fat deposition. The biosafety is evaluated in vitro at the cellular level, based on ISO‐10993, and further checked by animal study. We do believe that the TA could have a greater potential to be developed into a safe health supplement to manage obesity and for body‐weight control.